STRATEGI DAKWAH PADA MASYARAKAT PLURAL: di Desa Wonorejo Kecamatan Banyuputih Kabupaten Situbondo - Aminul Alimin (Indonesian Journal of Islamic Communication, 2019)
In the context of community life, the “plurality” of religions or pluralism is often controversial which can disrupt the intergrity of society. There is no plural society that can be free of ethnic and communal tensions. Wonorejo Village community is a plural society, consisting of four ethnic tribes and four different religions, but community life is full of togetherness. This study aims to test empirically the focus of the problems that have been written are: What are the activities of propaganda in plural communities in the Village District Wonorejo Banyuputih Situbondo? What is the strategy of dakwah in plural society in Wonorejo Village, Banyuputih Sub-District, Situbondo Regency? The theoretical study used to base research activities under the title “Strategy of Dakwah on Plural Society in Wonorejo Village Banyuputih Sub-District of Situbondo Regency” is about dakwah strategy and plural society, while the methodology used to answer from the focus of this research problem is qualitative research with study approach case, this research was conducted in Wonorejo Village, Banyuputih District, Situbondo Regency, to complete the data of this research using observation, interview and documentation. Analysis of qualitative data used to analyze data. The results of the analysis show that Wonorejo Village is a village that still upholds customs and ancestral heritage. Based on the of this study obtained the conclusion: a). That dakwah activity in plural society in Wonorejo Village is the form of: preaching bi al-hal, pioneering Islamic activity, commemoration of Islamic Day, establishing Islamic education institution, preaching with community empowerment, dakwah through community institution or mass organization, cultural dakwah. b). The Dakwah strategy for plural society in Wonorejo Village is to use cultural infiltration strategy, ta`lim strategy or education, sentimental strategy and recitals strategy. Keywords: Strategy of Dakwah, Plural Society.